A Descriptive Analysis of the Leadership Practices of Primary School Principals in Promoting Sustainability Through Motivating Teachers - Khumalo Shuti Steph (Discourse and Communication for Sustainable Education, 2021)
Enhancing sustainability in primary schools is apposite because primary schools are the building blocks in any education system. In its examination, the study provides insights on the role of primary school principals in promoting sustainable education through inspiring teachers. Teacher motivation is a very critical focus research area, particularly in the present depressing times and particularly in promoting sustainability. Without ignoring and dismissing other factors that have a bearing on the poor performance of the South African primary schools, teacher discouragement is one of the factors. The purpose of this investigation was to explore the extent in which the leadership practices of primary school principals promote teacher motivation and ultimately achieving sustainable teacher workforce. This study was based on random sampled primary school teachers in South Africa, Waterberg District. Hundred and fifty survey questionnaires were distributed to participating primary schools and only 96 responses were received. The respondents were from a mix of both male and female teachers who responded to the questionnaire. Descriptive statistics was applied to analyse data. Even though the results indicated that there were issues with teacher motivation, to a significant extent, the majority of respondents demonstrated that most primary principals do take efforts in trying to ensure that teachers are motivated. The results of the study deepen the already existing scope of knowledge regarding teacher motivation, particularly in primary schools.